Actions for the Optimization of Russian – Indian Trade Cooperation - A. D. Bondarenko (Vestnik MGIMO-Universiteta)
The article describes current stage of the Russian-Indian trade-economic cooperation. The Author analyses the issues which business have to face approaching the markets of Russia and India. Special emphasis is laid on the measures for the optimization of cooperation.